2015
DOI: 10.1097/mat.0000000000000187
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of the eSVS Mesh

Abstract: In coronary artery bypass graft surgery, saphenous vein graft (SVG) patency is much lower than that of the internal mammary artery (IMA). To address this problem, an external support device, the eSVS Mesh was developed. A prospective randomized First-in-Man feasibility trial was conducted in 90 patients after institutional ethics committee approval at seven international centers. The left IMA was used to bypass the anterior descending artery. A mesh-supported (treated) saphenous vein was randomized to either t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…A non-constrictive Dacron ® sheath reinforced with PTFE ribs failed to improve patency due to frequent thrombosis, likely because of stent rigidity or oversizing, resulting in kinking [45]. To date, the most successful effort for improving vein graft patency is eSVS ® (Kips Bay Medical Inc.), consisting of a flexible kink-resistant nitinol mesh that received marketing authorization for patients undergoing coronary artery bypass grafting, which was consistently reported as safe [46]. However, enthusiasm was moderated as the outcomes of studies on graft patency following coronary bypass were contradictory.…”
Section: Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…A non-constrictive Dacron ® sheath reinforced with PTFE ribs failed to improve patency due to frequent thrombosis, likely because of stent rigidity or oversizing, resulting in kinking [45]. To date, the most successful effort for improving vein graft patency is eSVS ® (Kips Bay Medical Inc.), consisting of a flexible kink-resistant nitinol mesh that received marketing authorization for patients undergoing coronary artery bypass grafting, which was consistently reported as safe [46]. However, enthusiasm was moderated as the outcomes of studies on graft patency following coronary bypass were contradictory.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…However, enthusiasm was moderated as the outcomes of studies on graft patency following coronary bypass were contradictory. While some showed a patency up to 100 % [47,48], others demonstrated that the patency rate of mesh-supported grafts ranged from 28 to 49 % after 9-12 months [14,46,49]. It was suggested that trials had confusing confounding variables other than the evaluation of the mesh that could impact results.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Although there is some promise with ongoing clinical trials utilizing a braided Phynox mesh (Fluent, Vascular Graft Solutions) to support vein grafts in CABG and a Nitinol mesh to support fistulas for hemodialysis patients (VasQ, Laminate Medical), a recent clinical trial reinforcing vein grafts in CABG with a Nitinol mesh (eSVS Mesh, Kips Bay Medical) was terminated due to lower patency rates. It is possible that this also may have been due in part to tissue buckling or kinking …”
Section: Design Considerations For External Stentingmentioning
confidence: 99%
“…[2][3][4] The long-term efficacy of arterial revascularization especially of the left internal thoracic artery (LITA) on the left anterior descending (LAD) has been proven in many stu-dies. 5,6 Although the harvesting of venous graft material was felt to be easier and several items were developed to improve the quality of the veins, 7 venous grafts often show occlusion rates of 5 to 10% per year. 8 Therefore, long-term durability is often comparably bad.…”
Section: Introductionmentioning
confidence: 99%